Equine-assisted activities and therapies: enhancing the social worker's armamentarium. Issue 5 (3rd July 2016) - Acri, Mary; Hoagwood, Kimberly; Morrissey, Meghan; Zhang, Shirley
Abstract: Introduction: Equine-assisted activities and therapies (EAAT) have gained prominence as a viable therapeutic approach for a range of mental health and developmental problems, yet is not widely known and not conventionally provided within the social work educational curriculum. Thus, the purpose of this study is to provide a review of various certification bodies available to social workers in order to bring EAATs into their therapeutic work. Methods: A multi-stage process, including consultation with experts in the field and an online search was undertaken to locate certification programs for mental health professionals. Results: Seven certification organizations were identified; programs varied with respect to mental health pre-requisites, type of certification, training components, and cost. Discussion: There has been substantial growth in EAAT for children with mental health and developmental problems, and there are a range of certification types to select from. Factors to consider when choosing which type of certification to pursue, and barriers to certification are discussed.